New life for Nixies [in digital clocks]. - Zorpette, G.
Novel digital clocks get their glamour from the Nixie tube, the mother of electronic numerical displays.
Keywords: Nixie tube; Digital clocks; Diodes; Electronic numerical displays; Time-keeping circuit